A Comprehensive 3D geological model of the North-Eastern sector of the San Leo plateau - Donati, Davide; Francioni, Mirko; Chiacchio Gotardo, Olivia; Lucente, Claudio Corrado; Borgatti, Lisa (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value="{"1":2,"2":"The town of San Leo, situated in the northern Apennines of Italy, is subject to slope instability phenomena due to its geological/structural setting. The 3D geological model of the eastern sector of the San Leo rocky plateau has been developed through the integration of data obtained from laser scanning and digital photogrammetric surveys along with core drilling geomechanical analysis. The geological features have been\rintegrated into one single model that enables the visualization of all structural features of the plateau, including superficial and in-depth discontinuities. The model highlights how the area rear of the northeastern scarp, formed by the 2014 landslide event, is highly fractured, whereas the eastern cliff presents lower fracture intensity. Two possible collapse scenarios have been simulated in relation to the fracture analysis that as been carried and emulating the 2014 failure mechanism, that involved a rock volume around 330.000 m3. The analysis of persistence of the fractures involved in these scenarios indicate that such events appear not to be imminent at the present time."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The town of San Leo, situated in the northern Apennines of Italy, is subject to slope instability phenomena due to its geological/structural setting. The 3D geological model of the eastern sector of the San Leo rocky plateau has been developed through the integration of data obtained from laser scanning and digital photogrammetric surveys along with core drilling geomechanical analysis. The geological features have been integrated into one single model that enables the visualization of all structural features of the plateau, including superficial and in-depth discontinuities. The model highlights how the area rear of the northeastern scarp, formed by the 2014 landslide event, is highly fractured, whereas the eastern cliff presents lower fracture intensity. Two possible collapse scenarios have been simulated in relation to the fracture analysis that as been carried and emulating the 2014 failure mechanism, that involved a rock volume around 330.000 m3. The analysis of persistence of the fractures involved in these scenarios indicate that such events appear not to be imminent at the present time.